MATRIX THEORY OVER DGC NUMBERS - Gurses, Nurten; Senturk, Gulsum Yeliz (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2023)
Classical matrix theory for real, complex and hypercomplex numbers is a well-known concept. Is it possible to construct matrix theory over dual-generalized complex (DGC) matrices? The answer to this question is given in this paper. The paper is constructed as follows. Firstly, the fundamental concepts for DGC matrices are introduced and DGC special matrices are defined. Then, theoretical results related to eigenvalues/eigenvectors are obtained and universal similarity factorization equality (USFE) regarding to the dual fundamental matrix are presented. Also, spectral theorems for Hermitian and unitary matrices are introduced. Finally, due to the importance of unitary matrices, a method for finding a DGC unitary matrix is stated and examples for spectral theorem are given.
Keywords: dual-generalized complex number; matrices over special rings; eigenvalues and eigenvectors; fundamental matrix; Science & Technology - Other Topics